AN ANALYSIS OF PROMISCUITY IN EIMEAR MCBRIDE’S A GIRL IS A HALF-FORMED THING: AN ANALYSIS OF PROMISCUITY IN EIMEAR MCBRIDE’S A GIRL IS A HALF-FORMED THING - Putri Shinta Hasibuan; Parlindungan Purba (LINGUA : Jurnal Bahasa, Sastra, dan Pengajarannya, 2022)
This thesis is analyzing promiscuity on the main character. The purpose of this thesis is to find out and understand how it happened, to look for the two causes and impacts of promiscuity that are described in the novel. The main character is the girl is a victim of sexual violence by her own uncle. As a result of the vile things done by her uncle, She was involved in a deviation, namely promiscuity. She did promiscuity with lots of boys. The behavior of multiple partners in sexual relations without a commitment relationship (promiscuity) is rarely found in women. Because in general, women engage in sexual relations on the basis of love and as an expression of feelings of love towards their partners. When found by individual women with promiscuity behavior, it becomes interesting to look more deeply. The theory used to analyze is Theory by Kartono and Mcleish The research methods used in this thesis are qualitative methods and library research. The author collects data from the novel and from several sources of articles, books, and journals that have a relationship with this thesis. The results of this thesis are to reveal the truth that promiscuity can occur in the main character and get causes and impacts in their daily life.